Metal Catalysed Condensation Reaction - Saha, PK; Bahar, MH (Bangladesh Journal of Scientific and Industrial Research, 2007)
Propanone (acetone) was dimerised to obtain 4-hydroxy-4-methylpentanone-2 (diacetone alcohol) in reasonably good yields in presence of metal catalyst viz aluminium, iron, tin and zinc at different catalytic conditions---pure metal, activated metal and amalgamated metal. Yields of the product was found to decrease exponentially with the increase of proton number of the metal catalyst. Bangladesh J. Sci. Ind. Res. 42(1), 9-14, 2007